The Production of Shallots (Allium ascalonicum L.) in Response to the Application of Liquid Organic Fertilizer From Marine Fish Waste and Tithonia - Yopa Dwi Mutia; Aslan Sari Thesiwati; Ermawati Ermawati (JERAMI : Indonesian Journal of Crop Science, 2024)
Fish waste and Tithonia diversifolia are the essential ingredients of organic fertilizer. Several researchers have already tested these two materials, which have high plant nutrient content. This study aims to determine the effect of liquid organic fertilizer from marine fish waste and tithonia application on shallot (Allium ascalanicum L.) production. The research was conducted in Kuranji Subdistrict, Kuranji District, Padang City, West Sumatra, Indonesia, at 15 meters above sea level from November 2022 to March 2023. The experiment used a completely randomized design (CRD) with six treatments and four replications, resulting in 24 experimental units. The data were analyzed using analysis of variance (ANOVA) with a significance level of 5%. If there was a significant effect, Duncan's New Multiple Range Test was conducted at a significance level of 5%. The treatments consisted of 0, 10, 20, 30, 40, and 50 ml/L. The application of liquid organic fertilizer from marine fish waste and tithonia at 40ml/L is the most effective for shallot production, yielding the highest production per hectare at 12.13 tons/ha